2011
DOI: 10.1158/1055-9965.epi-11-0569
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of 5p12 As a Susceptibility Locus for Progesterone-Receptor–Positive, Lower Grade Breast Cancer

Abstract: Background The single nucleotide polymorphism 5p12-rs10941679has been found to be associated with risk of breast cancer, particularly estrogen receptor (ER)-positive disease. We aimed to further explore this association overall, and by tumor histopathology, in the Breast Cancer Association Consortium. Methods Data were combined from 37 studies, including 40,972 invasive cases, 1,398 cases of ductal carcinoma in situ (DCIS) and 46,334 controls, all of white European ancestry, as well as 3,007 invasive cases a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
27
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 12 publications
5
27
0
Order By: Relevance
“…Results from subgroup analyses on ER status of tumors were in agreement with previous reports [5], [25]. Findings from previous studies suggested that several SNPs are predominantly associated with ER-positive BC: 2q35-rs13387042 [22], TNRC9-rs3803662 [25], [37], 8q24-rs13281615 [38], FGFR2-rs2981582 [39]. The present findings support the notion that ER-positive and ER-negative tumors have different genetic components to their risks.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Results from subgroup analyses on ER status of tumors were in agreement with previous reports [5], [25]. Findings from previous studies suggested that several SNPs are predominantly associated with ER-positive BC: 2q35-rs13387042 [22], TNRC9-rs3803662 [25], [37], 8q24-rs13281615 [38], FGFR2-rs2981582 [39]. The present findings support the notion that ER-positive and ER-negative tumors have different genetic components to their risks.…”
Section: Discussionsupporting
confidence: 92%
“…Stratification of tumors by ER status indicated that the two SNPs (rs4415084 and rs10941679) on 5p12 confer risk, preferentially for ER-positive tumors, with no risk for ER-negative BC. Results from subgroup analyses on ER status of tumors were in agreement with previous reports [5], [25]. Findings from previous studies suggested that several SNPs are predominantly associated with ER-positive BC: 2q35-rs13387042 [22], TNRC9-rs3803662 [25], [37], 8q24-rs13281615 [38], FGFR2-rs2981582 [39].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results also suggest potential interaction between standardize age at first birth and rs10941679 (5p12) (P=0.04) in which the positive association was mainly observed in women with the variant (AG/GG) allele. rs10941679 has been frequently associated with breast cancer risk (7,24,25) and is in linkage disequilibrium with MRPS30 , a gene implicated in apoptosis and estrogen-receptor positive breast cancer (26,27). The biologic mechanisms which could cause an interaction between rs10941679 and standardized age at first birth have not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of analysis, 24 SNPs had been shown to be associated with BC risk, primarily through large population-based case–control studies (Supplementary Table 1) (Cox et al , 2007; Easton et al , 2007; Stacey et al , 2007, 2010; Ahmed et al , 2009; Thomas et al , 2009; Antoniou et al , 2010; Turnbull et al , 2010; Fletcher et al , 2011; Milne et al , 2011; Ghoussaini et al , 2012; Hein et al , 2012). We applied the pedigree RL approach to estimate SNP associations with BC risk using data from 736 families recruited on the basis of strong FH of BC and a set of unrelated unaffected controls.…”
mentioning
confidence: 99%